A green body of low-expansion high-transparency jade-quality ceramic rock plate and a preparation method thereof

CN123003256APending Publication Date: 2026-10-30广东嘉联企业陶瓷有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611249107.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0002]陶瓷岩板作为一种新型建筑装饰材料,凭借其大规格、薄型化、高硬度、耐磨等优异性能,近年来在建筑装饰、家居台面、背景墙等领域得到了广泛应用,但传统的陶瓷岩板不具有透光功能且膨胀系数较高,抗热性较差

Benefits of technology

1、本申请采用2-羟乙烷二膦酸对石英进行进一步地的改性,可以明显提高陶瓷岩板坯体的膨胀性能的同时还可以进一步地改善透明度和白度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003256A_ABST
    Figure CN123003256A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of ceramic rock plates, and particularly relates to a green body of a low-expansion high-transparency jade-quality ceramic rock plate and a preparation method thereof. The green body of the low-expansion high-transparency jade-quality ceramic rock plate comprises, in terms of mass fractions, modified quartz 15-25 parts, kaolin 10-25 parts, synthetic sintered mullite powder 10-20 parts, super-white ball clay 5-15 parts, bentonite 1-3 parts, frit 20-30 parts, and fluxing agent 1-5 parts. The ceramic rock plate green body prepared by using the specific modified quartz, synthetic sintered mullite powder, frit and fluxing agent has an expansion coefficient <4*10 ‑6 / ℃, a transmittance >=80%, and a whiteness >75°.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic slab technology, specifically relating to a blank for a low-expansion, high-transparency jade-like ceramic slab and its preparation method. Background Technology

[0002] As a new type of building decoration material, ceramic slabs have been widely used in building decoration, home countertops, background walls and other fields in recent years due to their excellent properties such as large size, thinness, high hardness and wear resistance. However, traditional ceramic slabs do not have light transmission function and have a high coefficient of expansion and poor heat resistance.

[0003] Currently, the applicant has a certain foundation in the research on translucent jade-like ceramic slabs. The applicant's previous Chinese patent application, authorized by announcement number CN115124322B, discloses a translucent white stone slab and its production process. The raw materials of the translucent white stone slab include 20-35 parts by weight of modified quartz, 13-15 parts by weight of high-white potassium sand, 15 parts by weight of water-milling material, 2 parts by weight of bentonite, 12 parts by weight of kaolin, and 20 parts by weight of ultra-white spherical clay. However, this formula is mainly a Si-Al-K-Na formula system, and the expansion coefficient of the green body after firing is relatively high.

[0004] In fact, achieving both low expansion and high light transmittance presents a significant technical challenge. To achieve high light transmittance, a larger amount of glassy phase and light-transmitting components needs to be introduced into the raw material, which often leads to an increase in the coefficient of thermal expansion of the raw material. Although existing technologies have ceramic slabs that claim to combine low expansion and high light transmittance, their expansion coefficients remain relatively high. For example, Chinese patent CN118791325B discloses a low-expansion, wear-resistant, high-light-transmitting, tightly-jointed ceramic slab and its preparation method. The slab is prepared from light-transmitting powder, the mineral composition of which includes, by mass percentage: 30-40% washed kaolin, 15-25% potassium feldspar, 25-35% high-alumina, high-calcium frit, and 10-25% wollastonite. The coefficient of thermal expansion of the light-transmitting raw material of this technology is 6.1 × 10⁻⁶ at 40-600℃. -6 / K~6.3×10 -6 / K. Summary of the Invention

[0005] To address the aforementioned problems, the present invention aims to provide a low-expansion, high-transparency jade-like ceramic slab blank and its preparation method. This invention utilizes specific modified quartz, synthetic sintered mullite powder, frit, and flux in combination to prepare a ceramic slab blank with an expansion coefficient <4×10⁻⁶. -6 / ℃, light transmittance ≥80%, whiteness >75°.

[0006] To achieve the above objectives, the present invention provides the following technical solution: The first aspect of this invention provides a blank for a low-expansion, high-transparency jade-like ceramic slab, wherein the raw materials, by weight, include: 15-25 parts modified quartz; 10-25 parts of kaolin; 10-20 parts of synthetic sintered mullite powder; 5-15 parts of super white clay; 1-3 parts bentonite; 20-30 parts of frit; Flux 1-5 parts.

[0007] Preferably, the modified quartz is prepared by adding pretreated iron-removed quartz into an ethanol solution of 2-hydroxyethanediphosphonic acid, sealing, stirring, heating, continuing stirring, and after stirring is completed, washing, filtering, and drying to obtain the modified quartz.

[0008] As a preferred method, the preparation method of the pretreated quartz for iron removal is as follows: quartz is ball-milled, and slurry is discharged and magnetic separation is performed every 15 minutes to remove iron. This process is repeated multiple times until the quartz particle size is ≤10μm and the Fe2O3 content is ≤1wt%. The quartz is then sprayed in a spray tower, aged, and the moisture content is ≤3%.

[0009] In its initial modification process, the applicant only performed ball milling and iron removal on quartz. While this improved the transparency and whiteness of the ceramic slab to some extent, it was not very effective in improving the expansion performance. The applicant discovered that further modification of quartz with 2-hydroxyethanediphosphonic acid (2-HWDI) significantly improved the expansion performance of the ceramic slab while also further enhancing its transparency and whiteness. This is likely because after 2-HWDI reacts with the hydroxyl groups on the quartz surface, the phosphorus-modified quartz can better combine with other components in the slab at high temperatures, optimizing the phase composition of the ceramic, effectively reducing the expansion coefficient of the slab, and simultaneously optimizing the microscopic refractive index matching inside the slab, reducing light scattering within the slab, thereby significantly improving the transparency and whiteness of the ceramic slab.

[0010] Preferably, the ethanol solution of 2-hydroxyethanediphosphonic acid has a mass concentration of 1-3%.

[0011] Preferably, the mass ratio of 2-hydroxyethanediphosphonic acid to pretreated iron-removed quartz in the ethanol solution of 2-hydroxyethanediphosphonic acid is 0.1-0.3:1.

[0012] As a preferred embodiment, the preparation method of the modified quartz is as follows: pretreated iron-removed quartz is added to an ethanol solution of 2-hydroxyethanediphosphonic acid, sealed, stirred at 6000-8000 rpm for 30-40 min, heated to 150-180℃, and stirred for 6-8 h. After stirring, the quartz is washed, filtered, and dried to obtain the modified quartz.

[0013] Preferably, the kaolin has a whiteness of 90 degrees or higher and an Fe2O3 content of less than 1 wt%.

[0014] Preferably, the Fe2O3 content of the synthesized sintered mullite powder is less than 1 wt%.

[0015] In the prior art, cordierite is added to improve the coefficient of thermal expansion of ceramic bodies. However, the applicant found that this resulted in poor transparency and whiteness of the ceramic slab bodies in the present application. In this application, synthetic sintered mullite powder is added. While improving the thermal expansion of the ceramic slab bodies, the introduction of the mullite crystal phase helps to optimize the internal microstructure of the bodies, reduce the light scattering interface, and make the light propagation inside the bodies more uniform, thereby improving the transparency and whiteness of the ceramic slab bodies.

[0016] Preferably, the whiteness of the ultra-white clay is above 75 degrees and the Fe2O3 content is less than 1 wt%.

[0017] Preferably, the bentonite has a whiteness of 75 degrees or higher and an Fe2O3 content of less than 1 wt%.

[0018] Preferably, the frit has the following chemical composition by weight percentage: SiO2 45-60%, Al2O3 8-15%, K2O 4-9%, B2O3 3.5-8%, Na2O 1-3%, MgO 1-3%, Li2O 2-3%, BaO 1-2%, with the balance being loss on ignition.

[0019] Preferably, the flux is composed of borosilicate, fluorite and diopside.

[0020] Preferably, the mass ratio of the borate, fluorite and diopside is 4-7:1-2:1-5.

[0021] Fused frit and flux play a crucial role in the preparation of ceramic slab blanks. They not only effectively reduce the sintering temperature of the ceramic slab blanks but also influence their low expansion and high translucency. This application screened a specific frit system and creatively employed a ternary composite flux of borosilicate-fluorite-diopside to achieve refractive index matching between the glassy and crystalline phases and suppression of the expansion coefficient at low-temperature sintering, resulting in a ceramic slab blank expansion coefficient <4×10⁻⁶. -6 / ℃, light transmittance ≥80%, whiteness >75°.

[0022] The second aspect of the present invention provides a method for preparing a blank of low-expansion, high-transparency jade-like ceramic slab, comprising the following steps: mixing kaolin, synthetic sintered mullite powder, ultra-white clay, bentonite, frit and flux, ball milling, slurry discharge, iron removal, sieving and classifying according to particle size of 80 mesh, 60 mesh and 40 mesh, spraying powder in a spray tower, aging, and spraying modified quartz into it to obtain the blank of low-expansion, high-transparency jade-like ceramic slab.

[0023] As a preferred method, sieving is classified according to particle size of 80 mesh, 60 mesh, and 40 mesh.

[0024] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. This application uses 2-hydroxyethane diphosphonic acid to further modify quartz, which can significantly improve the expansion performance of ceramic slab blanks while also further improving transparency and whiteness.

[0025] 2. In this application, by adding synthetic sintered mullite powder, the expansion properties of the ceramic slab blank are improved, while the transparency and whiteness of the ceramic slab blank are also improved.

[0026] 3. This application selected a specific frit system and creatively employed a ternary composite flux of borate-magnesium fluoride-diopside to achieve refractive index matching and expansion coefficient suppression between the glassy and crystalline phases under low-temperature sintering, resulting in an expansion coefficient of <4×10⁻⁶ for the ceramic slab. -6 / ℃, light transmittance ≥80%, whiteness >75°. Attached Figure Description

[0027] Figure 1 This is a photograph of the light transmittance of a blank prepared using the blank from Example 3. Figure 2 and Figure 3 The image shows the external inspection results of the ceramic slab prepared using the blank from Example 3. Detailed Implementation

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1 A blank for a low-expansion, high-transparency jade-like ceramic slab, comprising, by weight, the following raw materials: 15 parts modified quartz; 10 parts of kaolin; 10 parts of synthetic sintered mullite powder; 5 parts of super white clay; 1 part bentonite; 20 portions of frit; 1 part flux.

[0030] The modified quartz is prepared as follows: quartz is ball-milled, and slurry is discharged and magnetic separation is performed every 15 minutes to remove iron. This process is repeated multiple times until the quartz particle size is ≤10μm and the Fe2O3 content is ≤1wt%. The quartz is then sprayed with powder in a spray tower and aged until the moisture content is ≤3% to obtain pretreated iron-removed quartz. The pretreated iron-removed quartz is added to an ethanol solution of 2-hydroxyethanediphosphonic acid, sealed, and stirred at 6000rpm for 30 minutes. The temperature is raised to 1560℃ and stirring is continued for 6 hours. After stirring, the quartz is washed, filtered, and dried to obtain the final product.

[0031] The ethanol solution of 2-hydroxyethanediphosphonic acid has a mass concentration of 2%.

[0032] The mass ratio of 2-hydroxyethanediphosphonic acid to pretreated iron-removed quartz in the ethanol solution of 2-hydroxyethanediphosphonic acid is 0.2:1.

[0033] The whiteness of the kaolin is 91.7, and its chemical composition by weight percentage is: SiO2 49.41%, Al2O3 35.39%, MgO 0.31%, CaO 0.01%, Fe2O3 0.31%, TiO2 0.2%, K2O 0.55%, Na2O 1.51%, with the balance being loss on ignition.

[0034] The synthesized sintered mullite powder has an Al2O3 content of 45%, an Fe2O3 content of 0.4%, and a mullite phase content of 55%.

[0035] The whiteness of the ultra-white clay is 85.3, and its chemical composition by weight percentage is: SiO2 53.85%, Al2O3 32.51%, MgO 0.21%, CaO 0.05%, Fe2O3 0.65%, TiO2 0.3%, K2O 0.83%, Na2O 0.01%, with the balance being loss on ignition.

[0036] The bentonite has a whiteness of 85 and a chemical composition by weight percentage: SiO2 67%, Al2O3 14%, MgO 0.1%, CaO 0.01%, Fe2O3 0.5%, K2O 1.5%, Na2O 2.9%, SbO2 0.53%, with the balance being loss on ignition.

[0037] The chemical composition of the fused block by weight percentage is: SiO2 58%, Al2O3 13%, K2O 8%, B2O3 7%, Na2O 3%, MgO 3%, Li2O 2%, BaO 1%, with the balance being loss on ignition.

[0038] The flux is composed of borosilicate, fluorite and diopside.

[0039] The mass ratio of the borate, fluorite, and diopside is 6:2:2.

[0040] The preparation method of the above-mentioned low-expansion, high-transparency jade-like ceramic slab blank includes the following steps: mixing kaolin, synthetic sintered mullite powder, ultra-white clay, bentonite, frit and flux, ball milling, slurry discharge, iron removal, sieving and classifying according to particle size of 80 mesh, 60 mesh and 40 mesh, spraying powder in a spray tower, aging, and spraying modified quartz into it to obtain the low-expansion, high-transparency jade-like ceramic slab blank.

[0041] Example 2 A blank for a low-expansion, high-transparency jade-like ceramic slab differs from Example 1 only in that, by weight parts, the raw materials include: 20 parts modified quartz; 20 parts of kaolin; 15 parts of synthetic sintered mullite powder; 10 parts of super white clay; 2 parts bentonite; 25 portions of frit; Three parts flux; everything else is the same.

[0042] Example 3 A blank for a low-expansion, high-transparency jade-like ceramic slab differs from Example 1 only in that, by weight parts, the raw materials include: 25 parts modified quartz; 25 parts of kaolin; 20 parts of synthetic sintered mullite powder; 15 portions of super white clay; 3 parts bentonite; 30 portions of frit; Five parts flux; everything else is the same.

[0043] Comparative Example 1 The difference between this comparative example and Example 3 is that the modified quartz is pretreated quartz with iron removed; all other aspects are the same.

[0044] Comparative Example 2 The difference between this comparative example and Example 3 is that, by mass parts, the raw materials include: 25 parts modified quartz; 25 parts of kaolin; 15 portions of super white clay; 3 parts bentonite; 30 portions of frit; Five parts flux; all others are the same.

[0045] Comparative Example 3 The difference between this comparative example and Example 3 is that, by mass parts, the raw materials include: 25 parts modified quartz; 25 parts of kaolin; 20 parts cordierite powder; 15 portions of super white clay; 3 parts bentonite; 30 portions of frit; Five parts flux; all others are the same.

[0046] Comparative Example 4 The difference between this comparative example and Example 3 is that the frit, by mass percentage, includes: SiO2 91%, Al2O3 2%, CaO 2%, MgO 1%, K2O 1%, Na2O 3%; the rest are the same.

[0047] Comparative Example 5 The difference between this comparative example and Example 3 is that the frit, by mass percentage, includes: SiO2 39.89%, Al2O3 27.4%, Fe2O3 0.09%, TiO2 0.02%, CaO 12%, MgO 1.7%, K2O 5.8%, Na2O 9.8%, BaO 1.1%, with the balance being loss on ignition; all other components are the same.

[0048] Comparative Example 6 The difference between this comparative example and Example 3 is that the flux is composed of borosilicate and diopside in a mass ratio of 8:2; all other aspects are the same.

[0049] Comparative Example 7 The difference between this comparative example and Example 3 is that the flux is composed of fluorite and diopside in a mass ratio of 8:2; all other aspects are the same.

[0050] Comparative Example 8 The difference between this comparative example and Example 3 is that the flux is composed of borosilicate and fluoromagnesia in a mass ratio of 6:4; all other aspects are the same.

[0051] Performance Test 1: Green bodies were prepared using the green bodies from the above embodiments and comparative examples: the mass ratio of 80 mesh, 60 mesh, and 40 mesh green bodies was 5:3:2. A mixture of 80 mesh and 60 mesh raw materials was prepared and set aside. A mold was used, and a layer of 40 mesh mixed raw material was laid at the bottom, followed by a layer of 80 mesh and 60 mesh mixed raw material on top of the 40 mesh raw material. During the laying of the 80 mesh, 60 mesh, and 40 mesh materials, modified quartz was evenly sprayed and distributed between the mixed raw materials using a powder spraying method. The mixture was pressed into a 10 mm thick shape, dried, fired at 1150°C, and polished to obtain a ceramic slab green body. The following performance tests were then conducted: 1. Coefficient of expansion: Tested according to standard GB / T 3810.8 (20-600℃); 2. Light transmittance: Tested according to standard GB / T3296; 3. Whiteness: Tested using a digital whiteness meter.

[0052] Table 1 ; As can be seen from Table 1, the ceramic slab blanks prepared in Examples 1-3 have a coefficient of thermal expansion of <4×10⁻⁶. -6 / ℃, transmittance ≥80%, whiteness >75°; A photograph of the ceramic slab blank in Example 3 showing its transmittance is shown below. Figure 1 As shown.

[0053] In Comparative Example 1, the unmodified quartz, which only underwent iron removal pretreatment, resulted in a significantly larger coefficient of thermal expansion and a decrease in light transmittance in the obtained ceramic slab blank. In Comparative Example 2, where no synthetic sintered mullite powder was present, the coefficient of thermal expansion of the resulting ceramic slab blank was significantly increased, and the light transmittance decreased. In Comparative Example 3, when synthetic sintered mullite powder was replaced with cordierite powder, the coefficient of thermal expansion of the resulting ceramic slab blank decreased, but the translucency and whiteness significantly decreased. When Comparative Examples 4 and 5 were replaced with other frits, the coefficient of expansion of the resulting ceramic slab blanks increased significantly, and the light transmittance decreased. Comparative Examples 6-8 showed that changing the flux composition significantly increased the coefficient of thermal expansion of the resulting ceramic slab blanks.

[0054] Performance Test 2 Ceramic slabs were prepared using the blanks from Example 3: 80-mesh, 60-mesh, and 40-mesh blanks were mixed in a mass ratio of 5:3:2. The 80-mesh and 60-mesh raw materials were prepared and set aside. A mold was used, and the 40-mesh raw material was laid as the bottom layer, followed by the 80-mesh and 60-mesh raw material. During the laying of the 80-mesh, 60-mesh, and 40-mesh blanks, modified quartz was evenly sprayed and distributed between the raw materials using a powder spraying method. The slabs were pressed into shape to a thickness of 10 mm, dried, glazed, and ink-sprayed, then fired at 1150°C, and polished to obtain the ceramic slabs. The finished ceramic slabs were sent for external testing, and the results were as follows: Figure 2 and Figure 3 As shown.

[0055] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A raw material for a low-expansion, high-transmittance jade-like ceramic slab, characterized in that, By weight, the raw materials include: 15-25 parts modified quartz; 10-25 parts of kaolin; 10-20 parts of synthetic sintered mullite powder; 5-15 parts of super white clay; 1-3 parts bentonite; 20-30 parts of frit; 1-5 parts flux; The modified quartz is prepared by adding pretreated iron-removed quartz into an ethanol solution of 2-hydroxyethanediphosphonic acid, sealing, stirring, heating, continuing stirring, and after stirring is completed, washing, filtering, and drying to obtain the modified quartz.

2. The blank for the low-expansion, high-transparency jade-like ceramic slab according to claim 1, characterized in that, The coefficient of thermal expansion of a 10mm thick ceramic slab blank prepared from the aforementioned low-expansion, high-transparency jade-like ceramic slab blank is <4×10⁻⁶. -6 / ℃, light transmittance ≥80%, whiteness >75°.

3. The blank for the low-expansion, high-transparency jade-like ceramic slab according to claim 2, characterized in that, The method for preparing the pretreated quartz for iron removal is as follows: quartz is ball-milled, and slurry is discharged and magnetic separation is performed every 15 minutes to remove iron. This process is repeated multiple times until the quartz particle size is ≤10μm and the Fe2O3 content is ≤1wt%. The quartz is then sprayed in a spray tower, aged, and the moisture content is ≤3%.

4. The blank for the low-expansion, high-transparency jade-like ceramic slab according to any one of claims 1-3, characterized in that, The whiteness of the kaolin is above 90 degrees, and the Fe2O3 content is less than 1 wt%.

5. The blank for the low-expansion, high-transparency jade-like ceramic slab according to claim 4, characterized in that, The Fe2O3 content of the synthesized sintered mullite powder is less than 1 wt%.

6. The blank for the low-expansion, high-transparency jade-like ceramic slab according to claim 5, characterized in that, The whiteness of the ultra-white clay is above 75 degrees and the Fe2O3 content is less than 1 wt%; the whiteness of the bentonite is above 75 degrees and the Fe2O3 content is less than 1 wt%.

7. The blank for the low-expansion, high-transparency jade-like ceramic slab according to any one of claims 1-3, characterized in that, The chemical composition of the fused block by weight percentage is: SiO2 45-60%, Al2O3 8-15%, K2O 4-9%, B2O3 3.5-8%, Na2O 1-3%, MgO 1-3%, Li2O 2-3%, BaO 1-2%, with the balance being loss on ignition.

8. The blank for the low-expansion, high-transmittance jade-like ceramic slab according to claim 7, characterized in that, The flux is composed of borosilicate, fluorite and diopside.

9. The blank for the low-expansion, high-transparency jade-like ceramic slab according to claim 8, characterized in that, The mass ratio of the borate, fluorite and diopside is 4-7:1-2:1-5.

10. A method for preparing the blank of the low-expansion, high-transparency jade-like ceramic slab according to any one of claims 1-9, characterized in that, The process includes the following steps: mixing kaolin, synthetic sintered mullite powder, ultra-white clay, bentonite, frit, and flux; ball milling, slurry discharge, iron removal, and sieving according to particle sizes of 80 mesh, 60 mesh, and 40 mesh; spraying powder in a spray tower; aging; and finally spraying modified quartz into the mixture to obtain the raw material for low-expansion, high-transparency jade-like ceramic slabs.

Citation Information

Patent Citations

  • A translucent white stone slab and its production process

    CN115124322B

  • Low expansion, wear-resistant, high light transmittance, dense seam and continuous grain ceramic rock plate and preparation method thereof

    CN118791325B